1994
DOI: 10.1109/tcomm.1994.577085
|View full text |Cite
|
Sign up to set email alerts
|

On the number of wavelengths and switches in all-optical networks

Abstract: Abstract-We consider optical networks using wave-a signal launched from a transmitter may arrive at a valength division multiplexing, where the path a signal riety of receivers on many different wavelengths and/or takes is determined by the network switches, the wavearrive at a receiver on several different wavelengths. length of the signal, and the location the signal originated. Therefore, a signal is routed through a combination of circuit switching and wavelength routing (asthe number of available waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In a reconfigurable network with w available wavelengths, Barry and Humblet [1994] showed that the number of wavelength-independent 2 ϫ 2 switches required to support permutation routing is ⍀(n log(n/w 2 )). 1 For the special case in which the transmitters are fixed-tuned and the receivers are tunable, Pieris and Sasaki [1993] showed that the number of wavelength-independent 2 ϫ 2 switches required for permutation routing is ⍀(n log(n/w)), and constructed such a network using O(n log(n/w)) wavelength-independent switches.…”
Section: Introductionmentioning
confidence: 99%
“…In a reconfigurable network with w available wavelengths, Barry and Humblet [1994] showed that the number of wavelength-independent 2 ϫ 2 switches required to support permutation routing is ⍀(n log(n/w 2 )). 1 For the special case in which the transmitters are fixed-tuned and the receivers are tunable, Pieris and Sasaki [1993] showed that the number of wavelength-independent 2 ϫ 2 switches required for permutation routing is ⍀(n log(n/w)), and constructed such a network using O(n log(n/w)) wavelength-independent switches.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in [20], approximate analytical expressions for overall blocking probabilities have been derived for various network topologies. Barry and Humblet [30] have derived a lower bound on the number of switching states in a network with wavelength converters. In [31], it is shown that wavelength converters causes insigni®cant reduction in blocking probability at light loads, whereas at medium loads, the gain is signi®cant.…”
Section: Related Workmentioning
confidence: 99%
“…Multiplexing is widely employed due to its capability to increase transmission capacity and to reduce system costs [2]. There are three basic types of multiplexing technique in communication systems; time division multiplexing (TDM) [4][5][6], frequency or wavelength division multiplexing (FDM) [3,7] or (WDM) [8][9][10], and code division multiplexing (CDM) [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%